Tactics and Strategies for Managing Ebola Outbreaks and the Salience of Immunization. (10th February 2015) - Getz, Wayne M.; Gonzalez, Jean-Paul; Salter, Richard; Bangura, James; Carlson, Colin; Coomber, Moinya; Dougherty, Eric; Kargbo, David; Wolfe, Nathan D.; Wauquier, Nadia
Abstract : We present a stochastic transmission chain simulation model for Ebola viral disease (EVD) in West Africa, with the salutary result that the virus may be more controllable than previously suspected. The ongoing tactics to detect cases as rapidly as possible and isolate individuals as safely as practicable is essential to saving lives in the current outbreaks in Guinea, Liberia, and Sierra Leone. Equally important are educational campaigns that reduce contact rates between susceptible and infectious individuals in the community once an outbreak occurs. However, due to the relatively lowR 0 of Ebola (around 1.5 to 2.5 next generation cases are produced per current generation case in naïve populations), rapid isolation of infectious individuals proves to be highly efficacious in containing outbreaks in new areas, while vaccination programs, even with low efficacy vaccines, can be decisive in curbing future outbreaks in areas where the Ebola virus is maintained in reservoir populations.